Expansion and contraction of the Engraulis ringens spawning area in northern Chile - Moreno, Paola; Claramunt, Gabriel (Scientia Marina, 2022)
Many studies have considered the temporal patterns of reproduction of Engraulis ringens, but little attention has been given to the spatial patterns of reproduction (spawning areas), which have shown great variability in both location (geographical position) and extent (the area covered by positive stations), without a satisfactory explanation. Along the Chilean coast, the daily egg production method (DEPM) has been used for several years to estimate spawning biomass in the northern Chile E. ringens population, with 24 surveys being carried out from 1992 to 2020. The most fluctuating parameters estimated in the DEPM have been the location and extent of the spawning area and the average female weight. In the last few years the eggs were distributed near the coast, whereas in the first few years they showed a more oceanic distribution. The average female weight has fallen from 30 g in the 1990s to 11 g in the last few years. In the present study, we analysed the relationship of the location and extent of spawning areas with female size and abundancy in E. ringens from northern Chile. According to the results, periods of high abundancy of eggs are positively correlated with larger females that spawn in more oceanic zones and to the south, expanding the spatial egg distribution and increasing the egg density. By contrast, in years with low abundance of eggs, the spawning was located north and towards the coast, with a smaller spawning area and smaller female size.